Monastic economies in late antique Egypt and Palestine - Blanke, Louise; Cromwell, Jennifer (Cambridge University Press, 2023)
This book situates discussions of Christian monasticism in Egypt and Palestine within the socio-economic world of the long Late Antiquity, from the golden age of monasticism into and well beyond the Arab conquest (fifth to tenth century). Its thirteen chapters present new research into the rich corpus of textual sources and archaeological remains and move beyond traditional studies that have treated monastic communities as religious entities in physical seclusion from society. The volume brings together scholars working across traditional boundaries of subject and geography and explores a diverse range of topics from the production of food and wine to networks of scribes, patronage, and monastic visitation. As such, it paints a vivid picture of busy monastic lives dependent on and led in tandem with the non-monastic world.
This volume is the result of a conference organised by the editors and held on 16 and 17 March 2016 in Ertegun House, Oxford. Eighteen papers were presented at the conference, most of which have been included in the present volume. -- Preface
Keywords: Konferenzschrift -- 2016 -- Oxford; Politische Ökonomie; Mönchtum; Palästina; Ägypten; Ordensleben